Association between handgrip strength and mental health in Korean adolescents. (5th June 2021) - Hwang, In Cheol; Ahn, Hong Yup; Choi, Soo Jung
Abstract: Background and Objectives: Muscle strength is associated with adverse mental health outcomes in adults; however, few studies have examined this association among adolescents. This study investigated the association between handgrip strength and mental health in a nationally representative sample of Korean adolescents. Methods: We performed a cross-sectional study of 3530 adolescent (12–18 years old) from the 2014–2017 Korean National Health and Nutrition Survey. Handgrip strength was defined as the maximum measurement in kilograms from the dominant hand. Adverse mental health included the presence of perceived stress, depressive mood and suicidal ideation. Logistic regression models were used with adjustment for potential confounders. Results: The mean age ± SD of the study participants was 14.9 ± 2.0 years. Girls (47.5% of participants) had poorer mental health than boys. For boys, each 1-kg increase in handgrip strength was associated with a 3% decrease in the odds of having perceived stress and depressive moods. For girls, there was a positive association between handgrip strength and perceived stress. The relationship between handgrip strength and perceived stress was dose dependent for both sexes. Conclusions: Low handgrip strength was associated with poor mental health among boys. Future research is required to validate our findings and to establish whether interventions to increase muscular strength can reduce the prevalence of perceived stress and depressive mood in boys.